Influence of different dialysis modalities in the measurement of resting energy expenditure in patients with acute kidney injury in ICU - Góes, Cassiana R. de [UNESP]; Vogt, Barbara Perez [UNESP]; Sanches, Ana Claudia S. [UNESP]; Balbi, André L. [UNESP]; Ponce, Daniela [UNESP] (My University, 2017)
Background Currently, the execution of indirect calorimetry, which is considered the gold standard for measuring energy expenditure, is not indicate during dialysis, and it may interfere on nutritional therapy of these patients. This study aimed to evaluate the resting energy expenditure (REE) in patients with severe acute kidney injury treated by different modalities of dialysis and to identify whether dialysis influences on REE. Methods This was a prospective cohort study that evaluated patients admitted in intensive care units with diagnosis of acute kidney injury AKIN-3, mechanically ventilated, and submitted to conventional hemodialysis (CHD), extended hemodialysis (EHD) or high volume peritoneal dialysis (HVPD). Indirect calorimetry was performed at pre dialysis time and during the dialysis procedure. Parameters that could change REE were also evaluated. Results One-hundred patients undergoing 290 dialysis sessions were evaluated, with mean age 60.3 ± 17 years, 69% were male and 74% have died. There was no significant difference between REE of predialysis time and during dialysis time (2156 ± 659 kcal vs. 2100 ± 634 kcal, respectively, p = 0.15). No difference was observed in the REE before and during dialysis of different modalities. There were no differences between parameters pre and during dialysis of each modality. There was only a difference in norepinephrine dose, which was higher in pre dialysis time in HVPD and EHD modalities, compared with CHD modality. Moreover, during dialysis time, EHD modality had significantly higher VAD compared to other dialysis modalities. Conclusion The three evaluated modalities did not change REE. Indirect calorimetry can be performed during dialysis procedures and there was no difference between ventilation parameters, sedatives use, body temperature and VAD in both moments.
Keywords: Acute kidney injury; Dialisys; Energy expenditure; Indirect calorimetry; Intensive care